Analisa Perbandingan Konsumsi Bahan Bakar Pertamax dan Pertalite Pada Mobil Xpander Ultimate Automatic 2018 - Maulana, Calvin; Anwar, Moh.Syaiful (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Currently, public vehicles such as cars use several choices of fuel types for gasoline cars, including Pertamax and Pertalite. Car fuel consumption is influenced by several factors, including the type of fuel used. This study aims to determine the difference in car fuel consumption against the use of Pertamax and Pertalite fuel by conducting road tests in urban areas. Testing each type of fuel is tested with the full to full method to get a more accurate calculation, First the test will be carried out refueling Pertamax to full then to record the initial kilometer when going to do a road test, after recording a road test with the route Perum Tas II Tanggulangin Sidoarjo —-> Pasar Kapasan Surabaya —-> Jalan Kendangsari Surabaya —-> gas station Jalan Raya Ngaban Tanggulangin Sidoarjo . The total distance of the entire trip is 139 km after conducting a full to full road test obtained the following data 139: 13.67 = 10.16 km / liter. After a road test with the first fuel, gasoline is drained so that the fuel is not mixed. Then the car is filled with pertalite fuel, testing is carried out by the same method as during the Pertamax fuel road test. After conducting road tests with Pertalite obtained the following results 139: 13.80 = 10.07 km / liter. Conclusion Based on the results of research and discussion, it can be concluded : Pertamax fuel consumption is greater than Pertalite Â with a ratio of 10.16 km / liter and 10.07 km / liter. The difference that is not so noticeable occurs because of the similarity of parameters used such as: Max RPM limit, Average speed, The total distance that distinguishes is only the level of congestion, for traffic during the Pertamax test is relatively denser than during the Pertalite test.